The epistles of St John the Greek text with notes - Westcott, Brooke Foss, 1825-1901 (Grand Rapids, MI Eerdmans, 1966)
Includes bibliographical references, index and Greek text.
First published 1883.
Keywords: Bible. N.T. Epistles of John -- commentaries